2013
DOI: 10.1016/j.postcomstud.2013.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Distributive justice attitudes in Ukraine: Need, desert or social minimum?

Abstract: This paper presents research findings based on a factorial survey study of attitudes toward the justice of income distribution in Ukraine. The factorial survey design was used for the first time in a representative large-scale survey in Ukraine and provided an opportunity to investigate the effect of multiple factors concerning individual, family and enterprise characteristics in complex subjective evaluations of just earnings. The focus within this study lays on three fundamental principles, according to whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 28 publications
1
16
0
3
Order By: Relevance
“…A further note is that in all three datasets, there were similar effects for the other dimensions, indicating consensus regarding expected rewards for inputs and abilities such as education, occupation, and age. These findings are in line with the results of earlier studies (e.g., Jasso and Rossi, 1977;Alves and Rossi, 1978;Jasso and Meyersson Milgrom, 2008;Gatskova, 2013).…”
Section: Discussionsupporting
confidence: 93%
“…A further note is that in all three datasets, there were similar effects for the other dimensions, indicating consensus regarding expected rewards for inputs and abilities such as education, occupation, and age. These findings are in line with the results of earlier studies (e.g., Jasso and Rossi, 1977;Alves and Rossi, 1978;Jasso and Meyersson Milgrom, 2008;Gatskova, 2013).…”
Section: Discussionsupporting
confidence: 93%
“…Both of these examples show that justice judgments also reflect respondents' personal interests and that experience with the resolution of distributional conflicts (or lack of it) plays a crucial role. This is supported by Buzea et al (2013) and Gatskova (2013). Buzea et al (2013) found significant differences between students and the rest of the population, with the former leaning more toward the equal-distribution principle.…”
Section: Experience-based Attitudes: Attitudes Toward Justice and Thementioning
confidence: 69%
“…The numbers of dimensions used per vignette range from three (Jann, 2008) to ten Gatskova, 2013;Sauer et al, 2009). The number of vignettes to be evaluated varies much more.…”
Section: Figure 1 Example Vignette With Five Dimensionsmentioning
confidence: 99%
See 1 more Smart Citation
“…It cannot be claimed that the entire population has totally rejected radical nationalist ideology (either ethnic Ukrainian nationalism or pro-Soviet/Russian leftism). But the dominant discourse in the society has turned towards ideals of social redistributive justice or neo-liberal economic policies for everyone (Gatskova, 2013).…”
Section: Russian Model In Ukraine: Economic Basis Government and Popmentioning
confidence: 99%